(3EJaGbjI GdeTGQcI GdeUQjI GdChQHjI Hjf GdfXQjI h GdJWHjb (B/s - (3SGde, RjfH LGHQs ((3GdEScfOQjI(B: s (3OGQ GdhaGA dOfjG(B, s, 2007)
(3jVe JYQja HGdEJaGbjI hfHPI JGQjNjI YfgG, CgOGa GdEJaGbjI, GdSdY GdUfGYjI, GdSdY GdRQGYjI , GdSdY GdRQGYjI GdeUfYI hGdSejcI bhGYO GdefTC, eRGjG GdEJaGbjIs
Keywords: (3GJaGbjGJs; (3GdEJaGbjGJ GdJLGQjIs; (3eUQ(B- (3GdEJaGbjGJ GdJLGQjIs